2019
DOI: 10.1002/lary.28223
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity burden and nonclinical factors associated with sinonasal cancer all‐cause mortality

Abstract: Objective: To describe comorbidity burden and nonclinical factors associated with all-cause mortality of sinonasal cancer in the United States.Methods: The National Cancer Database (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) was queried for adult cases of sinonasal cancer (n = 10,518). Outcome of interest was all-cause mortality. Independent variables included comorbidity score and nonclinical factors such as age, gender, race, facility type, distance to facility, insurance, and income. Surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…Without these data to guide management, developing a unifying approach to this group of diseases has proven difficult and improvements in survival have remained elusive. [34][35][36][37] Consistent with prior work, 33,[38][39][40] we found that higher grade and T stage and increasing age and Charlson-Deyo comorbidity score were associated with worse survival. Several other factors also influence survival among patients with anterior skull base malignancies, 31,33,[38][39][40] but were not specifically explored in this study.…”
Section: Other Factors Influencing Survivalsupporting
confidence: 88%
“…Without these data to guide management, developing a unifying approach to this group of diseases has proven difficult and improvements in survival have remained elusive. [34][35][36][37] Consistent with prior work, 33,[38][39][40] we found that higher grade and T stage and increasing age and Charlson-Deyo comorbidity score were associated with worse survival. Several other factors also influence survival among patients with anterior skull base malignancies, 31,33,[38][39][40] but were not specifically explored in this study.…”
Section: Other Factors Influencing Survivalsupporting
confidence: 88%
“…[1][2][3][4] For patients with paranasal sinus cancer, race is associated with worse outcomes, including increased rates of nodal metastasis and worse disease-specific and overall survival. [5][6][7] The mechanism of this relationship is uncertain, although some studies have suggested that worse outcomes for certain demographic groups occur secondary to delayed presentation as well as suboptimal delivery of care. [8][9][10] Primary paranasal sinus cancers are rare, comprising only about 2% to 3% of head and neck cancer, with squamous cell carcinoma being the most common histologic diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…For head and neck cancer, age‐adjusted incidence is increased in some races, such as African Americans, and 5‐year survival rates tend to be lower overall despite similarities in care 1–4 . For patients with paranasal sinus cancer, race is associated with worse outcomes, including increased rates of nodal metastasis and worse disease‐specific and overall survival 5–7 . The mechanism of this relationship is uncertain, although some studies have suggested that worse outcomes for certain demographic groups occur secondary to delayed presentation as well as suboptimal delivery of care 8–10 …”
Section: Introductionmentioning
confidence: 99%
“…41,46 This is similar to the incidence peak of sinonasal malignancies, but differs from that of benign sinonasal lesions, which may occur at an earlier age. 56,57 Previous publications suggest that this tumor entity is found predominantly in females, and the presence of progesterone and estrogen in leiomyomas may contribute to this tumor's bias toward the female sex. 28,47 However, our study suggests that the incidence of sinonasal leiomyomas is evenly distributed among the sexes, with a slight male predominance (52.4%).…”
Section: Discussionmentioning
confidence: 99%